Mitochondria in Health and Diseases - Javadov, Sabzali (Cells, 2020)
Mitochondria are subcellular organelles evolved by endosymbiosis of bacteria with eukaryotic cells characteristics. They are the main source of ATP in the cell and play a pivotal role in cell life and cell death. Mitochondria are engaged in the pathogenesis of human diseases and aging directly or indirectly through a broad range of signaling pathways. However, despite an increased interest in mitochondria over the past decades, the mechanisms of mitochondria-mediated cell/organ dysfunction in response to pathological stimuli remain unknown. The Special Issue, “Mitochondria in Health and Diseases,” organized by Cells includes 24 review and original articles that highlight the latest achievements in elucidating the role of mitochondria under physiological (healthy) conditions and, in various cell/animal models of human diseases and, in patients. Altogether, the Special Issue summarizes and discusses different aspects of mitochondrial metabolism and function that open new avenues in understanding mitochondrial biology.